ADAMTS13: origins, applications, and prospects. Issue 10 (12th September 2018) - Plautz, William E.; Raval, Jay S.; Dyer, Mitchell R.; Rollins‐Raval, Marian A.; Zuckerbraun, Brian S.; Neal, Matthew D.
Abstract : ADAMTS13 is an enzyme that acts by cleaving prothrombotic von Willebrand factor (VWF) multimers from the vasculature in a highly regulated manner. In pathologic states such as thrombotic thrombocytopenic purpura (TTP) and other thrombotic microangiopathies (TMAs), VWF can bind to the endothelium and form large multimers. As the anchored VWF chains grow, they provide a greater surface area to bind circulating platelets (PLTs), generating unique thrombi that characterize TTP. This results in microvasculature thrombosis, obstruction of blood flow, and ultimately end‐organ damage. Initial presentations of TTP usually occur in an acute manner, typically developing due to an autoimmune response toward, or less commonly a congenital deficiency of, ADAMTS13. Triggers for TMAs that can be associated with ADAMTS13 deficiency, including TTP, have been linked to events that place a burden on hemostatic regulation, such as major trauma and pregnancy. The treatment plan for cases of suspected TTP consists of emergent therapeutic plasma exchange that is continued on a daily basis until normalization of PLT counts. However, a subset of these patients does not respond favorably to standard therapies. These patients necessitate a better understanding of their diseases for the advancement of future therapeutic options. Given ADAMTS13's key role in the cleavage of VWF and the prevention of PLT‐rich thrombi within the microvasculature, future treatments may include anti‐VWF therapeutics, recombinant ADAMTS13 infusions, and ADAMTS13 expression via gene therapy.